2010
DOI: 10.1109/tbme.2010.2080679
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Bayesian Classification of Healthy Controls, Bipolar Disorder, and Schizophrenia Using Intrinsic Connectivity Maps From fMRI Data

Abstract: We present a method for supervised, automatic and reliable classification of healthy controls, patients with bipolar disorder and patients with schizophrenia using brain imaging data. The method uses four supervised classification learning machines trained with a stochastic gradient learning rule based on the minimization of Kullback-Leibler divergence and an optimal model complexity search through posterior probability estimation. Prior to classification, given the high dimensionality of functional magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…Only 5 recent studies have tried to overcome this issue by introducing individual confidence measures. 39,48,54,56,57 As seen in Fig 2 and On-line larger body of independent work. The diversity of scientific backgrounds of recent studies is reflected by a striking heterogeneity of reported methodologic details, sample characteristics, validation strategies, and performance measures.…”
Section: Potential Clinical Applications and Integration In Diagnostisupporting
confidence: 56%
“…Only 5 recent studies have tried to overcome this issue by introducing individual confidence measures. 39,48,54,56,57 As seen in Fig 2 and On-line larger body of independent work. The diversity of scientific backgrounds of recent studies is reflected by a striking heterogeneity of reported methodologic details, sample characteristics, validation strategies, and performance measures.…”
Section: Potential Clinical Applications and Integration In Diagnostisupporting
confidence: 56%
“…Functional connectivity fMRI techniques (Friston, 2002) have emerged as useful and informative methods to test hypotheses about the integration of brain regions implicated as dysfunctional in psychiatric disorders. Despite promising functional connectivity results in adult bipolar disorder (e.g., Anand et al, 2009;Arribas et al, 2010;Calhoun et al, 2008b;Chepenik et al, 2010;Foland et al, 2008;Pompei et al, 2011;Wang et al, 2009), to the authors' knowledge, only two studies of functional connectivity in children with PBD have been published, and both utilized a seed voxel technique. In one study, amygdala connectivity with emotional face processing regions was attenuated during a facial emotion-rating task (Rich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a ROC analysis of each "binarized" problem (i.e. one class vs. the others) has been made, as it is done in [16]. The ROC space for each problem is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All these descriptors have been classified using a feedforward Artificial Neural Network [15] with one hidden layer, and softmax activation function in the hidden and output layers (to guarantee that outputs satisfy the probability constraints) [16].…”
Section: Classificationmentioning
confidence: 99%